Impact of ultra‐conservative ICD programming in patients with LVADs: Avoiding potentially unnecessary tachy‐therapies. Issue 2 (17th January 2022) - Robinson, Alexander; Parikh, Valay; Jazayeri, Mohammad‐Ali; Pierpoline, Michael; Reddy, Y. Madhu; Emert, Martin; Pimentel, Rhea; Dendi, Raghuveer; Berenbom, Loren; Noheria, Amit; Ramirez, Rigoberto; Sauer, Andrew J.; et al.
Abstract: Background: Patients with left ventricular assist devices (LVAD) often tolerate ventricular arrhythmias (VA). We aim to assess the frequency and outcomes of ICD therapies averted by ultraconservative ICD programming (UCP) in LVAD patients. Methods: This single center, retrospective cohort study included patients with LVADs and ICDs implanted from 2015 to 2019 that had UCP. The aim for UCP was to maximally delay VA treatments and maximize anti‐tachycardia pacing (ATP) prior to ICD shocks. VA events were reviewed after UCP and evaluated under prior conservative programming to assess for potentially averted events (that would have resulted in either ATP or defibrillation with prior programming). Results: Fifty patients were included in the study with follow‐up of median 16 ± 10.2 months after UCP. The median time from LVAD implantation to reprogramming was 7 days (IQR 5–9 days). Fourteen patients (28%) had potentially averted VA events that would have been treated with their prior ICD programming (82 total events, median two events per patient, IQR 1–10 events). Treated VA events occurred in 15 patients (30%). Eleven of the 14 patients with potentially averted VAs had treated events as well. Only one patient reported definitive symptoms of self‐limited "dizziness" during a potentially averted event that did not result in hospitalization. No patients died of complications from or needed emergent care/hospitalization due a potentially averted VA. Conclusions: UCP in LVAD patients likely prevented unnecessary VA treatments in many patients with minimal reported symptoms during these potentially averted events. Prospective studies are necessary to confirm these findings.